2003
DOI: 10.1002/mds.10605
|View full text |Cite
|
Sign up to set email alerts
|

Movement disorders in patients with peripheral facial palsy

Abstract: Acute unilateral facial paralysis is usually a benign neurological condition that resolves in a few weeks. However, it can also be the source of a transient or long-lasting severe motor dysfunction, featuring disorders of automatic and voluntary movement. This review is organized according to the two most easily recognizable phases in the evolution of facial paralysis: (1). Just after presentation of facial palsy, patients may exhibit an increase in their spontaneous blinking rate as well as a sustained low-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 61 publications
0
61
0
3
Order By: Relevance
“…This process generally begins three months after injury 11 . According to our data, however, the latency for developing HFS after PFP was of 28.9 months, a longer period than expected.…”
Section: Discussionmentioning
confidence: 99%
“…This process generally begins three months after injury 11 . According to our data, however, the latency for developing HFS after PFP was of 28.9 months, a longer period than expected.…”
Section: Discussionmentioning
confidence: 99%
“…A more common condition, hemifacial spasms can also be triggered by a VII nerve injury, usually by a mass lesion in the cerebellopontine angle but even in other sites related to the extra-cranial branches in the face [1][2][3] . Multiple pathophysiological mechanisms are probably involved, including abnormal branching after aberrant axonal regeneration and enhaced facial motoneural excitability 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Its etiology is usually unknown and it is known as idiopathic facial palsy or Bell palsy. However, it can cause transient or long lasting severe motor dysfunction and involuntary movement disorders (1).…”
mentioning
confidence: 99%
“…Indeed, electrophysiologic recordings performed in subsequent years showed that inputs carried by the afferent fibers of the trigeminal nerve ophthalmic branch in the paralytic side cause increased excitability of the blink reflex in the non-paralytic side and proved quantitatively that the same increase cannot be provided by the inputs carried by the afferent fibers in the non-paralytic side (5). In light of the studies, pathophysiologic mechanisms are based on the sensitization in polysynaptic pathways of the blink reflex and increased excitability in facial motor neurons (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation